Human Resource Management Concepts: Organizational Development, Remuneration Management and Organizational Sustainability - Anita, Siska Yuli; Suryaningsih, Lilik; Suhendra, Agus; Gani, Intan Maesti; Febrian, Wenny Desty (Dinasti Publisher, 2024)
The purpose of this literature research is expected to build a hypothesis regarding the influence between variables that can later be used for further research in the scope of human resource management. The literature review research article on the concept of human resource management: organizational development, remuneration management and organizational sustainability is a scientific literature article in the scope of human resource management science. The approach used in this literature review research is descriptive qualitative. The data collection technique is to use literature studies or conduct a review of relevant previous articles. The data used in this descriptive qualitative approach comes from previous research that is relevant to this research and is sourced from academic online media such as the Thomson Reuters Journal, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Web of Science, Sinta Journal, DOAJ, EBSCO, Google Scholar and digital reference books. In previous research, 1 relevant previous article was used to review each independent variable. The results of this literature review article are: 1) Organizational Development is related to the Concept of Human Resource Management; 2) Remuneration Management is related to the Concept of Human Resource Management; and 3) Organizational Sustainability is related to the Concept of Human Resource Management.